Vitamin E and Alzheimer’s disease: what do we know so far? - Browne D (Dove Medical Press, 2019)
Declan Browne, Bernadette McGuinness, Jayne V Woodside, Gareth J McKayCentre for Public Health, Queen’s University Belfast, Belfast, UKAbstract: Vitamin E has been proposed as a potential clinical intervention for Alzheimer’s disease (AD) given the plausibility of its various biological functions in influencing the neurodegenerative processes associated with the condition. The tocopherol and tocotrienol isoforms of vitamin E have multiple properties including potent antioxidant and anti-inflammatory characteristics, in addition to influences on immune function, cellular signalling and lowering cholesterol. Several of these roles offer a theoretical rationale for providing benefit for the treatment of AD-associated pathology. Diminished circulating concentrations of vitamin E have been demonstrated in individuals with AD. Reduced plasma levels have furthermore been associated with an increased risk of AD development while intake, particularly from dietary sources, may limit or reduce the rate of disease progression. This benefit may be linked to synergistic actions between vitamin E isoforms and other micronutrients. Nevertheless, randomised trials have found limited and inconsistent evidence of vitamin E supplementation as an effective clinical intervention. Thus, despite a strong rationale in support of a beneficial role for vitamin E for the treatment of AD, the evidence remains inconclusive. Several factors may partly explain this discrepancy and represent the difficulties of translating complex laboratory evidence and dietary interactions into clinical interventions. Methodological design limitations of existing randomised trials and restrictions to supplementation with a single vitamin E isoform may also limit the influence of effect. Moreover, several factors influence individual responsiveness to vitamin E intake and recent findings suggest variation in the underlying genetic architecture attenuates vitamin E biological availability and activity which likely contributes to the variation in clinical responsiveness and the failure of randomised trials to date. Importantly, the clinical safety of vitamin E remains controversial and warrants further investigation.Keywords: vitamin E, Alzheimer’s disease, tocopherols, tocotrienols, antioxidants